الصعوبات الإجرائية في إثبات الجريمة الإلكترونية في دولة الإمارات دراســـة تطبيـقيـة - زايد علي ناصر الجبري
This study aims to discuss the concept of electronic crimes in the United Arab Emirates, and the concept of the privacy policy for electronic applications. It identifies the process of investigating these crimes and the importance in dealing with them. The problem of this study lies in explaining the difficulties and procedural challenges facing judicial control officers within the scope and duties of the Dubai Police. The challenges lie in dealing with electronic information, how to confront it and what measures taken by enforcement in dealing with these modern crimes. The researcher relied on the descriptive approach, the analytical approach and the applied approach by reviewing local legislation in the United Arab Emirates, explaining the procedures used in combating electronic crimes by reviewing the books and specialized scientific references, university theses and relevant published research as well as the work of interviews conducted with the relevant authorities to achieve the goals of the study. The study has reached many results, the most important of which was the Emirati legislator in the authenticity of the electronic evidence that he has the physical authenticity in criminal proof, as well as the criminal investigator must have technical characteristics when investigating electronic crimes, and that privacy for users is one of the most important challenges that judicial control officers face. This study puts forward several recommendations, firstly, setting up specialized courts for cybercrimes consisting of judges and prosecutors specialized in the field of cybercrimes whom are expert how to deal with these type of cases, the necessity of involving experts and specialists in cybercrimes with legal scholars in enacting laws, as well as promote the level of cooperation between criminal investigation agencies in electronic crimes and the specialized companies that own electronic applications and websites. Besides that, granting the status of more legal power and control to electronic security and information security experts in the Dubai police. Finally, intensifying awareness campaigns about the security risks of the internet through various media on how to protect the netizens while using the internet, to protect privacy when using social media applications.